A core outcome set for genitourinary symptoms associated with menopause: the COMMA (Core Outcomes in Menopause) global initiative. Issue 8 (August 2021) - Lensen, Sarah; Bell, Robin J.; Carpenter, Janet S.; Christmas, Monica; Davis, Susan R.; Giblin, Karen; Goldstein, Steven R.; Hillard, Tim; Hunter, Myra S.; Iliodromiti, Stamatina; Jaisamrarn, Unnop; Khandelwal, Sunila; et al.
Abstract: Objective: Genitourinary symptoms, such as vaginal dryness and pain with sex, are commonly experienced by postmenopausal women. Comparing treatments for these genitourinary symptoms are restricted by the use of different outcome measures in clinical trials and the omission of outcomes, which may be relevant to women. The aim of this project was to develop a Core Outcome Set (COS) to be reported in clinical trials of treatments for genitourinary symptoms associated with menopause. Methods: We performed a systematic review of randomized controlled trials of treatments for genitourinary symptoms associated with menopause and extracted their outcomes. This list was refined and entered into a two-round modified Delphi survey, which was open to clinicians, researchers, and postmenopausal women from November 2019 to March 2020. Outcomes were scored on a nine-point scale from "not important" to "critically important." The final COS was determined following two international consensus meetings. Results: A total of 26 unique outcomes were included in the Delphi process, which was completed by 227 participants of whom 58% were postmenopausal women, 34% clinicians, and 8% researchers. Predefined thresholds were applied to the Delphi scores to categorize outcomes by importance, which informed the e consensus meetings, attended by 43 participants from 21 countries. The final COS includes eight outcomes: (1) pain with sex, (2) vulvovaginal dryness, (3) vulvovaginal discomfort or irritation, (4) discomfort or pain when urinating, (5) change in most bothersome symptom, (6) distress, bother or interference of genitourinary symptoms, (7) satisfaction with treatment, (8) side effects of treatment. Conclusion: These eight core outcomes reflect the joint priorities of postmenopausal women, clinicians, and researchers internationally. Standardized collection and reporting of these outcomes in clinical trials will facilitate the comparison of different treatments for genitourinary symptoms, advance clinical practice, and ultimately improve outcomes for symptomatic women. N/A: Video Summary: http://links.lww.com/MENO/A765 . Abstract : Supplemental Digital Content is available in the text